A model of customer-centric banking practices for corporate clients in Bangladesh - Andaleeb, Dr. Syed Saad; Rashid, Mamunur Harunur; Rahman, Quazi Akhlaqur (© 2016 Emerald Group Publishing Ltd., 2016)
This article was published in the International Journal of Bank Marketing [© 2016 Published by Emerald Group Publishing Ltd.] and the definite version is available at: http://doi.org/10.1108/IJBM-10-2014-0156 The Article's website is at: http://www.emeraldinsight.com/doi/full/10.1108/IJBM-10-2014-0156